HUBUNGAN PENGETAHUAN IBU DENGAN KEJADIAN DIARE PADA ANAK USIA 2-5 TAHUN DI WILAYAH KERJA PUSKESMAS MOMALIA KAB. BOLSEL 2016 - Andi Akifa Sudirman; Lenny Ali (-, 2021)
The study is used survey Analytical method and cross sectional approach. The population is the children aged 2-5 years old who are in the working area of momalia health centers. Technique of sampling is used accidental sampling, data collection is used quistionnaires while data analysis techniques used Chi-square. Results of research showed that 17 children (57%) had diarrhea of 17 mothers who have poor knowledge about diarrhea. Moreover, as many two children (6,0%) had diarrhea of 13 mothers who have a good knowledge about calculation statistical test of diarrhea with chi-square got p value =0,000 which means Ha failed rejected.